Six Wichita biking experiences: studying lived bicycling experiences to inform urban streetscape improvements for downtown Wichita - DeOrsey, Danielle S. (Kansas State University, 2015)
Human happiness is often overlooked in urban revitalization. Many studies have proven the benefits of regular exercise for overall health and happiness. Active transportation adopted as a major form of transportation has the potential to provide similar benefits. Wichita, Kansas, like many other mid-sized, American cities, prioritizes the car over the pedestrian. Currently, the plans for Douglas Avenue, the major thoroughfare, includes only minimal bicycle infrastructure, shared lane symbols (City of Wichita 2013). Lack of focus on the pedestrian and bicyclist only reinforces the auto-dominated downtown. Douglas Avenue is a missed opportunity and needs a re-envisioned strategy based upon current needs. I hypothesized that better understanding the lived biking experience of Downtown Wichita would help me to develop design recommendations that address current streetscape issues as they occur in daily life. This exploratory study documents the experiences of a small group of people who bicycle in or through downtown Wichita on a regular basis. First, participants recorded their experience visually and verbally by using GoPro cameras during a typical bike ride. Next, each participant reviewed their video with me, clarifying their comments and the overall experience. Dominant themes included: urban environment, bicycling infrastructure, road/traffic, safety and motorist behavior. The analysis of the bike rides and follow-up reflections were mapped over each participant’s route to reveal positive, negative, and neutral experiences categorized by theme. Final design strategies for selected areas (determined through analysis of experiences) were then produced based upon feedback and streetscape best practices. Bicyclists of Wichita are faced with many stressful situations during their daily routes. I have realized that downtown Wichita has more than a design problem to fix—an entire bicycle culture must be developed. I learned that while each participant was unique, they wanted the same things: safety, a pleasurable ride, and to be respected by motorists. Not all bicyclists’ needs can be answered through design; however, this proposal can help to create a safer and more pleasurable bicycling experience in downtown. An improved bicycle network provides humans with increased health, freedom to move, encourages and strengthens social connections, and provides a resilient form of transportation.
Keywords: phenomenology; biking; streetscape design; urban design; Design (0389); Transportation (0709); Urban Planning (0999)